PORE-SCALE SIMULATION STUDY OF WATERFLOODING IN DIGITAL ROCK MODELS OF NATURAL SANDSTONES WITH DIFFERENT PROPERTIES - T.R. Zakirov; A.S. Khayuzkin; N.V. Kalacheva; A.N. Kalimullina (Petroleum Engineering, 2026)
This paper investigates the displacement mechanics in a group of digital cores of natural sandstones with varying combinations of characteristics: reservoir properties, pore size distribution, Euler number, and fractal dimension. The key objective is to identify the relationship between these factors and the displacement characteristics. The «computational rock physics» technology which involves the conducting computational experiments in a digital model of pore space is used as a methodological basis. Calculations were performed using the lattice Boltzmann method for five models obtained by X-ray computed tomography on natural sandstone samples from deposits in the Republic of Tatarstan. The computational experiments reproduced the process of water injection into initially oil-saturated pore space under specified wetting condition, viscosity ratio, and capillarity number. Additionally, the selectivity of filling pores and throats of various sizes has been analyzed. A brief mathematical formulation of the problem is presented, as well as the results of the computational algorithm efficiency and parallelizing the software code. The examined models differed in their reservoir properties, pore space structure, and the degree of its heterogeneity. Connectivity of the injected phase was estimated based on the dynamics of the normalized Euler number, and the uniformity of the spatial distribution of porosity was estimated based on the fractal dimension. It was shown that pore space heterogeneity suppresses the displacement efficiency. An increase in heterogeneity contributes to a decrease in the connectivity of the aqueous phase in the pore space, as well as to an increase in injection selectivity. For a group of media with high heterogeneity, the displacement efficiency is controlled mainly by the uniformity of the porosity distribution, expressed through the fractal dimension. The dynamics of the water-oil interphase contact development is determined by the ratio of porosity to the average pore size. The dynamics of the water-skeleton contact surface development is not significantly affected by the heterogeneity of the pore space. The obtained relationships clarify the role of geometric and topological characteristics of the pore space in predicting the efficiency of flooding heterogeneous sandstone reservoirs. They can be used in interpreting the results of flow experiments and analyzing digital models of natural core samples.